Bacterial cellulose production by komagataeibacter nataicola TISTR 2661 by agro-waste as a carbon source - Churairat Moukamnerd (2020)
© 2020, Chiang Mai University. All rights reserved. To reduce the cost of obtaining bacterial cellulose (BC) and increase the value of fruit processing waste, the use waste from banana peel (BP) and passion fruit peel (PFP) as a carbon source for the production of bacterial cellulose (BC) by Komagataeibacter nataicola TISTR 2661 was developed. BP and PFP were digested with commercial saccharifying enzymes and the sugar content of these aqueous extracts reached 0.57±0.01 g/g-substrate (35.20±1.60 g/L) and 0.31±0.00 g/g-substrate (15.05±0.07 g/L), respectively. After 9 days of incubation, the BC production of BP and PFP aqueous extracts K. nataicola TISTR 2661 were 0.89±0.04 g/L and 0.31±0.07 g/L, respectively. To enhance the BC production, the aqueous extracts of BP and PFP were supplemented with MgSO4, KH2PO4 and (NH4)2HPO4. The addition of KH2PO4 1 g/L increased the BC production yield from BP aqueous extracts by 13.85±1.18%, which is higher than the yield from Hestrin & Schramn (HS) medium of 6.13±1.50%. The BC membrane was characterised by scanning electron microscope (SEM) and fourier-transform infrared spectroscopy (FTIR), which demonstrated that the aqueous extracts from BP and PFP could be used as carbon sources for the production of BC with low value residues.